Hydrochemical analysis and pollution assessment of the Anjiang underground river system in central Guizhou - Cui ZHAO; Hongliang QIN; Yuhua ZHU; Lin LUO; Miaoling HE; Zhonghua LI (地质科技通报)
Objective This study aims to establish a scientific framework for managing pollution in the Anjiang underground river system in central Guizhou and maintaining the ecological integrity of the Wujiang River basin. Methods The approach involves comprehensive hydrogeological surveys and analytical testing of water samples. We analyze hydrogeological conditions, apply the Shukarev classification system, utilize Piper's trilinear diagrams, conduct normality and Grubbs' tests, and calculate pollution indices. This investigation methodically examines the hydrogeological context, hydrochemical profiles, sources of major ions, background concentrations, and current pollution levels, and identifies the factors driving pollution in the Anjiang underground river system. Results The Anjiang underground river system covers approximately 18.91 square kilometers. The hydrochemical composition is classified into four types: HCO3·SO4-Ca, HCO3-Ca·Mg, HCO3·SO4-Ca·Mg, and SO4-Ca, each constituting roughly equal proportions. The predominant ions mainly originate from the dissolution of carbonate rocks, specifically dolomite from the Loushanguan Formation and limestone from the Qixia Formation-Maokou Formation, as well as sulfur-bearing minerals from the Longtan Formation. The pollution levels are significant, with total phosphorus, fluoride, and sulfate being the most crucial contaminants. Notably, the limestone aquifer of the Qixia Formation-Maokou Formation has higher pollution level than the dolomite aquifer of the Loushanguan Formation. This study confirms that the karst conduit network in the Anjiang underground river system has developed primarily within the Qixia Formation-Maokou Formation, with substantial secondary development in the Loushanguan Formation. The groundwater, enriched with inorganic pollutants such as total phosphorus, fluoride, and sulfate ions, flows northeast through karst conduits, contaminating the Anjiang underground river system. This polluted water eventually discharges into the Wujiang River via the S50 underground river outlet. Conclusion Our findings provide crucial theoretical support for the management and mitigation of pollution in karstic underground river systems.